Hayek versus Samuelson: Individual Freedoms and Economic Freedoms - (:unkn) unknown (BILGESEL YAYINCILIK SAN & TIC LTD, 2012)
Hayek versus Samuelson: Individual Freedoms and Economic Freedoms Friedrich von Hayek, a third generation Austrian School economist, argues that individual freedoms cannot exist without economic freedoms and that government intervention to economy leads to the loss of individual freedoms. However; despite his views on freedoms, Hayek did not hesitate to support dictators. According to a doubting Paul Samuelson a mixed economy may provide more individual freedoms than does a pure price economy and the type of efficient free markets championed by Hayek can only be maintained by use of power. In this work we focus on Hayek and analyze his views on free markets and freedoms by adopting the concepts of unknowability and liberal authoritarianism. We argue that some views of Hayek justify the use of force for achieving certain economic goals and that this use is necessary for the maintenance of the type of free market notion Hayek adopted.
Keywords: Friedrich von Hayek; Paul A. Samuelson; Austrian School of Economics